Electromyographic analysis of selected upper extremity muscles during jump throwing in handball - Taha, S. A.; Akl, A. R. I.; Zayed, M. A. (American Journal of Sports Science, 2015)
The purpose of this study was to determine upper extremity selected muscles activity of throwing performance in handball and work-loading to determine the percentage contribution of the muscles that more activation during throwing performance. Five male high level handball players participated in this study were (age: 20.5 ± 0.53 years; body mass: 81.00 ± 3.16 kg; height: 186.5 ± 3.69 cm). The EMG activity of the selected upper extremity muscles was measured using an 16-channel surface EMG system (ME6000 telemetric hardware system, Mega Electronics Ltd., FINLAND), Bipolar, Ag/AgCl surface electrodes (SKINTACT, FS-521), Innsbruck, Austria) were placed over the motor point of each muscle, and the EMG signals were acquired at a sampling rate of 1000 Hz with the MEGAWIN version 3.1-b12 software. Results showed the activities and arrangement of selected muscles were Deltoid muscle - medial part 1268.20±133.93 (38.70%), Flexor of the wrist 462.00±89.04 (16.30%), Flexor carpi ulnaris 439.30±33.87 (14.40%), Biceps brachii muscle 364.90±31.34 (12.90%), Rectus abdominis muscle 314.80±48.94 (9.70%), and Pectoralis major muscle 225.90±36.70 (8.00%). The rational for using sEMG to study muscle activation during a standardized jump throwing in handball is to provide a better understanding of muscle activation during this sport specific movement and muscle contributions during jump throwing in handball, and these data may be important for handball's coaches to jump throwing performance training.